2021
DOI: 10.1186/s12913-021-06534-w
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between insurance and health outcomes of diabetes mellitus patients in Maryland: a retrospective archival record study

Abstract: Background Past studies examining the health outcomes of diabetes mellitus (DM) patients found that social determinants of health disparities were associated with variabilities in health outcomes. However, improving access to healthcare, such as health insurance, should mitigate negative health outcomes. The aim of the study was to explore the association between four types of health insurance, namely, Medicare Fee-For-Service (FFS), Medicare Managed Care (MC), Private FFS, and Private MC plans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Diabetes mellitus is a common chronic disease in modern society, causing severe health and economic problems [137]. Decreasing postprandial hyperglycemia by delaying glucose absorption by inhibiting α-amylase and α-glucosidase in the digestive tract, is one of the therapeutic approaches to treating diabetes [138].…”
Section: Other Biological Activitiesmentioning
confidence: 99%
“…Diabetes mellitus is a common chronic disease in modern society, causing severe health and economic problems [137]. Decreasing postprandial hyperglycemia by delaying glucose absorption by inhibiting α-amylase and α-glucosidase in the digestive tract, is one of the therapeutic approaches to treating diabetes [138].…”
Section: Other Biological Activitiesmentioning
confidence: 99%
“…Such disparity is consistent with the literature that public insurance may be associated with barriers to timely and necessary care. 22,23 Individuals of non-Caucasian race were more likely to have public insurance and poor outcomes as well. 24 -26…”
Section: Discussionmentioning
confidence: 99%
“…Such disparity is consistent with the literature that public insurance may be associated with barriers to timely and necessary care. 22,23 Individuals of non-Caucasian race were more likely to have public insurance and poor outcomes as well. [24][25][26] Alternative approaches to DMCI have largely focused on dealing with pre-identified medications with high likelihood of requiring PA. 19 However, if an insurance's formulary list and PA criteria are frequently updated and not easily accessible, this approach can have limited impact.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the multivariate logistic regression analysis, the insured status, shock, mechanical ventilation, hypertension, and stroke were independent predictors of in‐hospital mortality among the study cohort. The evidence from Lee et al suggests that insurance plans were related to the health outcomes of elderly patients with DM 16 . Furthermore, Gold et al have shown that insurance coverage is related to improving the diagnosis and management of DM 14 .…”
Section: Discussionmentioning
confidence: 99%
“…There is a paucity of data describing the association between insurance status and in-hospital mortality of patients with hyperglycaemic crisis. Studies 16,17 only reported the association between insurance and health outcomes, such as length of stay and 30-day readmission, among patients with DM. We hypothesised that insurance status can influence in-hospital mortality of patients with hyperglycaemic crisis.…”
mentioning
confidence: 99%